Mental Health, Happiness, and Marital Satisfaction in U.S. Married Adults: A National Study and Practice Implications - Stafford, Stacy; Martin, Magy; Martin, Don (International Journal of Educational Studies, 2025)
This study examined whether personal happiness mediates the association between self-rated mental health and marital satisfaction among U.S. married adults. Addressing an underexplored mechanism, we tested a theoretically grounded mediation model using nationally representative data. The aim was to clarify whether happiness partially accounts for the pathway linking psychological functioning to relationship quality. Guided by Bowen Family Systems Theory, we conducted a quantitative archival analysis of the 2018 General Social Survey (N = 938 married adults). Variables were single-item Likert measures: mental health (HLTHMTNL), happiness (HAPPY), and marital satisfaction (HAPMAR). Analyses used IBM SPSS Statistics Version 29: multiple regression, path analysis, Baron and Kenny steps, and Sobel test; power estimated with G*Power 3.1. Mental health and happiness significantly predicted marital satisfaction (R² = .17). Mental health predicted happiness (b = 0.23, p < .001), and happiness predicted marital satisfaction (b = 0.35, p < .001). The direct effect of mental health on marital satisfaction remained significant but attenuated when controlling for happiness (b = 0.05, p = .011). The Sobel test indicated a significant indirect effect (b = 0.08, z = 8.49, p < .001). Findings support integrating happiness-enhancing strategies within couples counseling, especially when psychological distress is present. Brief positive psychology interventions (gratitude, savoring, acts of kindness) may complement systemic approaches to strengthen dyadic communication and resilience. Routine assessment of subjective happiness can inform case formulation, treatment planning, and progress monitoring in community mental health and private practice settings. To our knowledge, this is the first empirical test of happiness as a mediator between mental health and marital satisfaction using nationally representative U.S. data. The study advances family systems-informed models by quantifying a specific affective pathway and offers practice-relevant evidence for embedding well-being interventions alongside symptom reduction in couple-focused care.